SOME FOSSIL GINKGOPHYTES AND A POSSIBLE VOJNOVSKYALEAN ELEMENT FROM THE GLOSSOPTERIS FLORA OF VEREENIGING, TRANSVAAL - le Roux, S. F. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1970)
A short historical review is given of previously described sites where plant fossils occur in Lower Karroo beds at Vereeniging in the Southern Transvaal. Reference is made to the importance of these sites because of the outstanding discoveries made here in the past. Some new material from the same sites is described and several unusual elements in the Glossopteris flora of Vereeniging are recorded for the first time. Leaves of a plant not previously recorded from Gondwanaland are provisionally described under the term cf Nephropsis on account of a strong resemblance to leaves of the Russian Permian genus Nephropsis Zalessky. The remaining specimens in the assemblage are tentatively placed in the genera Ginkgoites Seward and Psygmophyllum Schimper respectively. Owing to the paucity of material, type numbers are assigned in certain cases, instead of specific names. Specific identification is attempted, however, in the case of four of the specimens, which are provisionally assigned to Psygmophyllum kidstoni Seward.